1999
DOI: 10.1177/030089169908500104
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in Frozen Section Interpretation: A Retrospective Study of Palpable Breast Tumors

Gábor Cserni

Abstract: Although the number of errors is relatively low, more stress should be placed on the preoperative diagnosis of breast lesions. Breast surgery frozen section should be used as rarely as possible for diagnostic purposes, despite the generally good diagnostic accuracy. However, it is reasonable to use frozen sections widely until the given preoperative diagnostic tools allow an appropriate preoperative workup, because it is the only way to keep histopathologists trained to interpret frozen sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Collective analysis shows that among experienced cytopathologists, the false‐positive rate varies between 0% and 0.86%, with an average rate of 0.17% 2, 9, 11, 22–27. This is close to the frequence observed in our series (0.25%) that, in addition, is comparable to the false‐positive rate reported on frozen sections 28–30…”
Section: Discussionsupporting
confidence: 85%
“…Collective analysis shows that among experienced cytopathologists, the false‐positive rate varies between 0% and 0.86%, with an average rate of 0.17% 2, 9, 11, 22–27. This is close to the frequence observed in our series (0.25%) that, in addition, is comparable to the false‐positive rate reported on frozen sections 28–30…”
Section: Discussionsupporting
confidence: 85%
“…In a series of 556 FS from the breast, Rosen reported no FPs, 3% FNs and 5.4% deferred diagnoses 27 . Others have estimated the FP rate for FS to be close to 1% and the deferred diagnosis rate to be up to 5% 28,29 …”
Section: Frozen Section As a Diagnostic Toolmentioning
confidence: 99%
“…Previous research showed that the diagnostic sensitivity of frozen section for ductal carcinoma in situ (DCIS) was only about 50% [8] , the main reason was that some DCIS appear as non-mass lesions, which could not be identi ed by macroscopic examination, that may be leading to sampling errors [8,9] . In our study, the diagnostic sensitivity of frozen section for pure DCIS was 50.62% (papillary carcinomas are not included), which similar to previous study.…”
Section: Discussionmentioning
confidence: 99%
“…However, its sensitivity in the diagnosis of very early breast cancer has been controversial. According to previous reports, the diagnostic accuracy of frozen section for invasive breast cancer is high [5][6][7] , but lower for carcinoma in situ [8][9][10] . So far, as far as we know, there is no study that investigated the role of frozen section in the diagnosis of CNB-undiagnosable breast cancer, therefore, its practical utility in CNB-undiagnosable breast cancer is indeterminate.…”
Section: Introductionmentioning
confidence: 99%